Split Hopkinson Tension Bar and Universal Testing Machine for High-Speed X-ray Imaging of Materials under Tension - Puneeth Jakkula; Amitay Cohen; Bratislav Lukić; David Levi-Hevroni; Alexander Rack; Georg Ganzenmüller; Stefan Hiermaier (Instruments, 2022)
Studying the failure behaviour of engineered or natural materials under dynamic loading scenarios is of high importance, for example to investigate the fracture mechanics and to prevent catastrophic failures of constructions. When dynamic loading is coupled to high-speed X-ray imaging, not only surface information but images of the interior of the specimens during failure are accessible. Here, a custom designed Split Hopkinson Tension Bar (SHTB) coupled a Universal Testing Machine (UTM) has been developed, dedicated to study quasi-static and dynamic response using ultra-high speed X-ray phase contrast imaging. Both systems follow a compact design which allows them to be temporarily installed at a synchrotron beamline. A brief description of the installation and usage of these setups are outlined. Selected example applications outline the potential of these systems. Both systems can be considered for proposal experiments at beamline ID19 of the European synchrotron ESRF on request.